ON THE WAY OF PROVIDING THE HEALTH OF LIGHTS (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
This article contains information about production measures to ensure the health of luminaries in our country, as well as information about the work carried out as a result of these measures. In the article, the work of provisioning, which is carried out to provide the religious with medical drugs, is expressed.